Amine-Catalyzed Three-Component Cascade Reaction between Alcohols or Thiols, Activated Alkenes, and Enones: A Simple and Chemoselective Synthesis of Densely Functionalized Compounds - Sun, Haiyun; Zhang, Bo; Chen, Xiangyu; He, Zhengjie (Synthesis, 2017)
A highly chemoselective three-component cascade reaction among alcohols or thiols, electron-deficient alkenes, and α,β-unsaturated ketones takes place under the catalysis of triethylamine, providing densely functionalized chain products in 44–99% yields. The transformation presumably proceeds through a sequential cascade of hetero-Michael/Michael reactions.
Keywords: multicomponent reactions; hetero-Michael addition; alcohols; thiols; alkenes; enones